Restructuring and functional heads - Cinque, Guglielmo (Cartography of syntactic structures, 2006)
Collects the articles of Guglielmo Cinque of the University of Venice. This book is divided into two sections, the first on restructuring, a central topic in Romance syntax and with connections to other language groups as well. The second part focuses on the consequences of treating clausal functional heads as members of a universal hierarchy.